Petrographic and geochemical characteristics of The Kiejo, Rungwe and Ngozi volcanic rocks, southern Tanzania: implication for tectonic activities and magmatic differentiation - Macheyeki, Athanas S. (Tanzania Journal of Science, 2021)
Rock samples were collected from the Kiejo, Rungwe and Ngozi volcanoes, southern Tanzania. Results show that, in the Ngozi and Rungwe volcanoes, magma cooled relatively fast. After large part of the magma had crystallized, nucleation of crystals at a relatively slow rate crystallized from interstitial fluids of the primary magma that had already crystallized fine grained minerals resulting into large grains of minerals. In the Kiejo volcano, both zoned and unzonned olivine crystals exist; unzoned crystals being primary and the zoned ones are secondary. Such observations also indicate that the magma responsible for these rocks had interstitial fluids that crystallized into olivine of different chemical and grain sizes. The lack of olivine, and the presence of orthopyroxene, the high amount of SiO2 wt% ( 63) as well as (Na2O + K2O) wt% 9.38 in the Ngozi volcano, indicate that the volcanic rocks in the Ngozi volcano are a result of a relatively silica saturated magma source. Otherwise, the magma could have originated from deeper in the crust such that it became contaminated with continental crust materials as it was erupting. Based on the Alikali-Silica diagram of Le Bas et al. (1986), the Ngozi and Rungwe magma contents fall in the field of trachy-dacite, and those from the Kiejo volcano fall in the field of basaltic trachy-andesite and basaltic magma. Such a pattern highlights close genetical and ?structural relationship of the magma that formed the three volcanoes. Keywords: Kiejo, Rungwe, Ngozi, volcanic rocks, Southern Tanzania.